Different ways of classifying drums with reference to illustrations and positioning of drum illustrations - Kjellström, Rolf (Scripta Instituti Donneriani Aboensis, 1991)
The focus of this paper is on the traditional Saami hunting in relation to the animal and hunting motifs on their drum, more specifially the southern Saami drums. One may wonder if it is possible for anyone to interpret a picture unconditionally. One has a certain ground of one's own to stand on and the question arises of whether this is the correct position, when -as in the present case — we approach another culture. We naturally include the experiences of our own culture in interpretations of another culture. The animal which is the commonest species on the southern Saami drums, is the reindeer. Other animals that occur are elks, wolves, beavers, foxes, snakes, among others. Considering the Saamis' hunting weapons, the most important of these were the bow and arrow, and the spear or spear shaft. Of these weapons it is the bow which is most often portrayed on drums. Also some trapping implement like a gin may appear on a drum, but in general we have little or no information about hunting or trapping methods at all.